Environmental and Social Management System Implementation Handbook : Construction - International Finance Corporation (Washington, DC, 2014)
This Handbook is intended to be a practical guide to help companies in the construction industry develop and implement an environmental and social management system, which should help to improve overall operations. In the current economic climate, companies are under pressure to perform or even just survive. New initiatives are often met with resistance as people struggle to keep up with their day-to-day responsibilities. Some people think that an environmental and social management system must be big, complicated and expensive. But that is not really true. To be effective, a management system needs to be scaled to the nature and size of the company. If a company has existing management systems for quality or health and safety, this Handbook will help to expand them to include environmental and social performance. Sections I and II provide background on environmental and social management systems (ESMS) in the construction industry. Section III provides step-by-step instructions on how to develop and implement an ESMS. The ESMS Toolkit and Case Studies section gives: 1) tools to help develop and implement the systems described in the Handbook; and 2) case studies presenting two companies in the construction industry that implemented an ESMS. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.